Hubungan Kecerdasan Emosional Dengan Tingkat Kecemasan Dalam Menyusun Tugas Akhir Pada Mahasiswa Tingkat Akhir Institut Kesehatan Dan Bisnis St. Fatimah Mamuju - Manuntungi, Andi Ernawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2022)
Anxiety is a sense of worry, nervousness, and even anxiety about something uncertain and can coexist, affect or cause depression. Anxiety experienced by students is related to external factors such as anxiety due to lack of knowledge in preparing the final project, delaying time due to many activities outside the final project so that it disrupts the development of the final project, and so on. The anxiety that students feel when dealing with final assignments can affect performance and graduation rates, because in this condition a person will experience a state of distortion of information processing that can interfere with the ability to be able to focus attention, reduce memory functions and others. Anxiety can arise as one of the body's physiological responses to be able to anticipate a problem that might come as a disturbance if it arises excessively. Until now, anxiety is also still a public disease. This study aims to determine the relationship between emotional intelligence and anxiety levels in preparing final assignments in final year students of St. Fatimah Mamuju Health and Business Institute in 2023. The type of research used in this study is a quantitative approach, using a cross sectional design. Sample 63 using total sampling technique. Data obtained by questionnaire and then analyzed by statistical tests. The results showed that based on the chi square test the p value = .725 <0.05, which means that there is no significant relationship between emotional intelligence in preparing the final project in final year students.